Prevalence of Impaired Joint Position Sense in Patients with Plantar Fasciitis: A Cross-Sectional Study - Sharvari J. Rao; Saumya Srivastava; Harramb Mittal (International Journal of Physiotherapy, 2024)
Background: The plantar fasciitis is a degenerative condition involving recurrent microtears and compromised biomechanics. It affects the Pacini and Ruffini corpuscles, which play a crucial role in proprioception. Compensation methods prompted by pain and alterations in biomechanics may compromise the joint position sense of the ankle joint. The study aims to determine the prevalence of impaired joint position sense in plantar fasciitis patients using smartphone apps. Methods: The study included 43 patients aged 20-50 years, encompassing both genders, with 28 females and 15 males. Patients with knee and ankle pathologies were not included in the study. The ankle joint position sense of the patients was measured using a smartphone application called Sensor Kinetics Pro 2.1.2, which provided angular velocities in three planes (X, Y, Z). The statistical analysis was carried out using SPSS 20.0, where a p-value of < 0.05 is considered statistically significant. Results: Of 43 patients with plantar fasciitis, the prevalence percentage of impaired joint position was 32.6%. Further, the joint position sense, as found in the application, was affected in the three planes (X, Y, Z) with a prevalence of 27.9%, 32.6%, and 39.5%, respectively. Conclusion: The present study concludes that joint position sense affects patients with plantar fasciitis; however, further studies should be conducted to generalize the results.